Modelling of Maxwell’s equations using uniform finite elements - Moiseenko, V.E. (Вопросы атомной науки и техники, 2003)
The theory of numerical stability of weighted residuals schemes for Maxwell’s equations written in terms of electric field is presented. Basing on it, the numerically stable scheme using physical components of electric field and uniform trial functions is developed. The proposed scheme is tested in cylindrical geometry and compared with the numerically stable Galerkin scheme. The tests show the evidence of numerical stability of the scheme proposed. The convergence is monotonic and corresponds to the order of approximation. It is demonstrated that, unlike the Galerkin scheme, the scheme proposed is much less sensitive to the stiffness of the Maxwell’s equations in plasma.